A novel and improved hydrophilic vanadium oxide-based cathode for aqueous Zn-ion batteries. (10th September 2020) - Zhang, Qiang; Zhang, Yi; Fu, Liangjie; Liu, Sainan; Yang, Huaming
Highlights: A novel strategy to prepare a self-supporting cathode with multifunctional. High hydrophilicity can improve the electrochemical performance of Zn-ion batteries. Providing a new way to develop sepiolite in electrochemical energy storage. Abstract: The preparation of cathode materials for aqueous Zn-ion batteries (ZIBs) with excellent electrochemical properties is an attractive research focus. However, the large size and high polarization of hydrated zinc ions limit the diffusion kinetics of Zn 2+ /electron, and the side reactions in the system also affect the performance of the battery. Herein, we present a novel hydrophilic self-supporting composite cathode for aqueous ZIBs, which employs V10 O24 ·12H2 O as active materials, acid-treated natural sepiolite and carbon nanotubes as structural and interfacial modifiers. It is demonstrated that the devices exhibit a high specific capacity of 191 mAh g −1 at a current density of 500 mA g −1 (93.6% retention after 100 cycles) and excellent rate performance. This good electrochemical performance is mainly related to the formation of hydrophilic surface/interface, the design of self-supporting and the good conductivity of the composite electrode. Specifically, the addition of acid-treated natural sepiolite and carbon nanotubes could improve the mechanical properties, hydrophilicity and the conductivity of electrode materials, respectively, making this strategy a promising choice for ZIBs. Graphical abstract: Image, graphical abstract